(untitled) (Iraqi National Journal of Earth Science (INJES), 2026)
Phosphogypsum is a by-product of the reaction of sulfuric acid with concentrated phosphate ores to produce phosphoric acid, the latter being the most important acid in the production of all types of phosphate fertilizers. This process takes place in the Iraqi General Phosphate Company in Al-Qaim District, west of Iraq. Phosphogypsum waste is disposed of in large quantities, and the increase and accumulation of this material requires large basins to absorb and preserve, therefore, the use of phosphogypsum in construction industries leads to its disposal. Mineral analyses showed that phosphogypsum is composed of gypsum. Chemically, phosphogypsum consists of (CaO=33.3) (SO3=44.6) (H2O=20.05) and the rest of the oxides enter into the sulfate compounds. Phosphogypsum in the present study were used in gypsum board production by adding slime (the by-product of calcining the carbonate part of phosphate raw materials) at a ratio of (90 phosphogypsum: 10 slime), which is called the selected mixture. The suitability of mixture was evaluated by conducting physical tests, and the results were consistent with the Iraqi standard specifications (ISS, 2015). The mixture was tested by physical tests (compressive strength test (5.51 N/mm2) and fracture criteria (3.295 N/mm2). Phosphogypsum can also be used as a plaster material for interior wall cladding, and the results of the physical tests were consistent with the (ISS, 2015); compressive strength (5.74 N/mm2), fracture toughness (1.937 N/mm2), fineness (5.5-7.5), consistency (18 min), and standard texture (56.8-58.4) %. Mineralogical and chemical analyses were conducted on the approved mixes, which were in compliance with (ISS, 2015). The use of industrial waste, such as phosphogypsum and slime, not only alleviates environmental problems but also provides new resources for the construction industry and reduces the use of natural raw materials.